Fast Facts : Benign Prostatic Hyperplasia. - Kirby, R. S. (Roger S.) (Fast facts., 2011)
"Fast Facts: Benign Prostatic Hyperplasia" (6th edition) provides a concise and up-to-date overview of the pathophysiology, diagnosis and treatment of BPH, a condition that, while rarely life-threatening, can have a huge impact on a man's quality of life, with symptoms that include frequency, nocturia and incomplete bladder emptying. The book provides the latest data on the safety and efficacy of various treatment strategies, as well as new preventive considerations. It focuses on up-to-date practical information that will enable the patient and the primary care physician - who is becoming inc.